Asymmetric between oil prices and renewable energy consumption in the G7 countries. (1st July 2021) - Guo, Yaoqi; Yu, Chenxi; Zhang, Hongwei; Cheng, Hui
Abstract: Understanding the dynamic relationship between oil prices and renewable energy is beneficial to promoting the development of the renewable energy market and the transition from fossil fuels to renewable energy, which will finally protect the environment. Based on the data of G7 countries from 1980 to 2018, this paper analyzes the short-term and long-term dynamic relationship between oil prices and renewable energy consumption (REC) by using linear and nonlinear autoregressive distributed lag models under the condition of structural fractures and then discusses its asymmetric characteristics. The results show that, except for France and Germany, the oil prices of other countries have a significant asymmetric effect on REC, but there is great heterogeneity between the countries. Specifically, in Canada, the U.S., and Italy, a positive change in oil prices has a greater impact on REC than a negative change, whereas in England and Japan, the results are just the opposite. Therefore, based on the heterogeneity between countries and the long- and short-term dynamic relationships reflected in the research results, this paper further discusses the policy implications. Highlights: The asymmetric transmission effect of oil price on renewable energy consumption was studied. Using nonlinear autoregressive distributed lag (NARDL) method. There is a structural breakpoint and it is added to the model in the form of dummy variable. The abnormal situation in Germany and France may be due to the implementation of government policies. In the long run, oil price has statistical significance for renewable energy consumption in G7 countries.